ПСИХОЛОГІЯ СОЦІАЛЬНОЇ ПІДТРИМКИ ЖИТТЄДІЯЛЬНОСТІ ЖІНОК В УМОВАХ ДИНАМІЧНОЇ СОЦІОТЕХНІЧНОЇ СИСТЕМИ: ЕМПІРИЧНІ ДОСЛІДЖЕННЯ - Шевяков О. В.; Шрамко І. А.; Бабатенко О. В. (International Journal of Innovative Technologies in Social Science, 2019)
The purpose of the article is to find out the peculiarities of social support for women’s life in the conditions of dynamic socio-technical management system of nature management. Using the methods of electrocardiography and electro- oculography revealed the change of increasing fatigue in the work of subjects with the display video series of the automated sociotechnical system "Monitoring of environmental activity". We surveyed 350 subjects (operators, specialists, students with computer skills) aged 18 to 36 years (all women) before, during and after the use of the display automation systems of a dynamic automated control system. The total duration of the display activity did not exceed four hours of continuous operation. The forms, content and nature of the interaction and interaction of the components of the dynamic human-nature socio-technical system are characterized. The socio-psychological analysis of the tendencies of the development of such socio-technical system is carried out. In the empirical study the features of psychological interaction of women with display video sets are identified. The concept of social support of their life activity at work with display video sets of dynamic continuous information is developed. The dependence of the level of computer readiness of women and the quality of perception of information from different forms of presentation is established. It is found that the quality of perception of information is affected not only by the level of computer readiness, but also by the total time of acquaintance with the computer, as well as the time spent at work on the computer. From the point of view of the subsystem of the reflective-modeling information activity of the designer, its technical and aesthetic attractiveness contributes to increasing attention to the information message, which directly influences the perception of the user. A positive correlation between techno-aesthetic appeal and the rememberability of the information message has been identified. More aesthetically pleasing information messages are able to arouse interest in the user, best performing informative and informative functions.